PENDUGAAN STOK KEPITING BAKAU HIJAU (Scylla serrata) HASIL TANGKAPAN NELAYAN DARI DESA KUBU KECAMATAN KUBU KABUPATEN KUBU RAYA KALIMANTAN BARAT - Ramadani, Chandriki; padmarsari, widadi; inpurwanto, inpurwanto (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACTScylla serrata fishing activities in the waters of Kubu Village are conducted continuously by fishermen and it can cause the mangrove crabs to thin out and can cause scarcity. The purpose of this study is to estimate S. serrata's green mangrove crabs, which include sex ratio , carapace width frequency, relationship between carapace width and weight, growth pattern, mortality rate and exploitation rate of S. serrata mangrove crabs. Data and samples were collected in September-December 2018 obtained from the two collectors located in Kubu Village. Analysis of the data processing of this study uses the FISAT II software program (FAO-ICLARM Stock Assessment Toll II). The variables to be observed are sex ratio, carapace width and crab weight, water surface temperature. The results showed that the sex ratio of male and female S. serrata crabs in the waters of Kubu Village was 1.69: 1. The distribution of male carapace crabs in the size of 123.5-130.5 mm, while females were in a wide range of 109.5 -116.5 mm. Analysis of the width and weight relationship produces positive allometric growth patterns in males, and isometrics in females. Male crab has an asymptotic width (Lâˆž) 220 mm, with a growth coefficient value of 0.24 per year, female mangrove crabs have an asymptotic width (Lâˆž) of 218 mm with a growth coefficient of 0.18 per year. The rate of exploitation of male crab is 0.3414 and female is 0.4223 the utilization is still below the optimal value. Keywords: Scylla serrata, Gender Ratio, Growth Pattern, Exploitation.